z transform convolution

Statement :

If  x1(n) * x2(n) ↔ X1(Z)  * X2(Z)         


Proof :
  
              
y (n)   = ∑      x(k) h(n-k)
            k=-∞

                            
y(z)  =             [     x(k) h(n-k) ] Z-n
                n=-∞    k=-∞

                  ∞                         ∞
y(z)  =       ∑      x(k) Z-k      ∑  h(n-k)  Z-(n-k)
                k=-∞                n=-∞

n=l and k=0 in second terms;

                  ∞                       ∞
y(z)  =       ∑      x(k) Z-k    ∑  h(l)  Z-l
                k=-∞                l=-∞


Y(z) = X(Z) H(Z)

Popular Posts